SOX9 is expressed in human fetal prostate epithelium and enhances prostate cancer invasion. - Wegner, Michael; et al. (Cancer Research, 2008)
SOX9 is a transcription factor that plays a critical role in the development of multiple tissues. We previously reported that SOX9 in normal human adult prostate was restricted to basal epithelium. SOX9 was also expressed in a subset of prostate cancer (PCa) cells and was increased in relapsed hormone-refractory PCa. Moreover, SOX9 expression in PCa cell lines enhanced tumor cell proliferation and was β-catenin regulated. Here we report additional in vivo results showing that SOX9 is highly expressed during fetal prostate development by epithelial cells expanding into the mesenchyme, suggesting it may contribute to invasive growth in PCa. Indeed, SOX9 overexpression in LNCaP PCa xenografts enhanced growth, angiogenesis, and invasion. Conversely, short hairpin RNA-mediated SOX9 suppression inhibited the growth of CWR22Rv1 PCa xenografts. These results support important functions of SOX9 in both the development and maintenance of normal prostate, and indicate that these functions contribute to PCa tumor growth and invasion. ©2008 American Association for Cancer Research.
UnivIS-Import:2015-03-09:Pub.2008.med.IB.LPCIPDBI.sox9is